Static Analysis of Stretching and Strengthening Exercises on Balance and Strength in the Elderly: Literature Review - wijianto, wijianto; Hidayatullah, Muhammad Furqon; Riyadi, Slamet; Bramastia, Bramastia (Universitas Muhammadiyah Surakarta, 2024)
Introduction: The literature review study is motivated by the presence of physiological changes indicating a decline in balance and strength in the elderly, considering gender differences. This is attributed to the overall decline in various body systems, including balance and muscle strength, in the elderly. The decrease in muscle quality or strength in the elderly has implications for mobility. Methods: The literature review method was applied to five articles obtained from several databases, namely EBSCO, PubMed, and Springer Link. The search keywords for articles included stretching exercise, elderly balance, elderly strength, and resisted exercise for the elderly. The researcher used